Effect of Stretching of Spastic Elbow Under Intelligent Control in Chronic Stroke Survivors—A Pilot Study - Rao, Sanjana; Huang, Meizhen; Chung, Sun Gun; Zhang, Li-Qun (Frontiers in Neurology, 2021)
Objective: To assess the short-term effects of strenuous dynamic stretching of the elbow joint using an intelligent stretching device in chronic spastic stroke survivors. Methods: The intelligent stretching device was utilized to provide a single session of intensive stretching to the spastic elbow joint in the sagittal plane (i.e., elbow flexion and extension). The stretching was provided to the extreme range safely, with control of the stretching velocity and torque to increase the joint range of motion (ROM) and reduce spasticity and joint stiffness. Eight chronic stroke survivors (age:52.6±8.2 years) completed a single one-hour intervention session. Elbow passive and active ROM, strength, passive stiffness (quantifying the non-reflex component of spasticity), and instrumented tendon reflex test of the biceps tendon (quantifying the reflex component of the spasticity) was measured before and after stretching. Results: After stretching, there was a significant increase in passive ROM of elbow flexion(p=0.021) and extension (p=0.026). Also, elbow active ROM and the spastic elbow flexors showed a trend of an increase in their strength. Conclusion: The intelligent stretching had a short-term positive influence on the passive movement ROM. Thereby may potentially be used to stretch spastic elbow joints repeatedly and regularly and subsequently help reduce upper limb impairments post stroke.